Comparison of molecular analysis results determined by next-generation sequencing to immunohistochemical indicators and clinicopathological parameters in prostate adenocarcinomas - Merve Çırak Balta; İbrahim Halil Erdoğdu; Esin Oktay; Nil Çulhac (Indian Journal of Pathology and Microbiology)
Background: Prostate cancer is a common cancer in males, frequently leading to mortality. Multiple genetic factors play roles in prostate cancer pathogenesis. Demonstration of pathological pathways and customised treatment options have been possible with next-generation sequencing. Aim: In this study, we aimed to evaluate the relationships of the changes in the prostate cancer pathways genes with the pathological, immunohistochemical and the clinical parameters. Study Design: Retrospective cross-sectional study. Materials and Methods: Among the prostate needle biopsy materials investigated in Adnan Menderes University Faculty of Medicine, Department of Pathology, thirty-one cases, who had been analysed using the next-generation sequencing system, were included in this study. Results: As a result of statistical analysis, a significant relationship was found between the pathogenic mutation detected in androgen receptor and Breast Cancer Gene 2 genes and tumour volume. In all cases with a pathogenic mutation in the androgen receptor gene, a pathogenic mutation in the Protein Tyrosine Phosphatase and Tensin Homolog gene was also observed and a significant relationship was found between them. Castration resistance was observed in cases with high tumour volume, and a statistically significant difference was found. A statistically significant relationship was found between tumour volume and Ki-67 expression. In addition, a significant relationship was observed between the castration resistance and Ki-67, c-erbB2 expressions. A statistically significant relationship was found between Ki-67 and c-erbB2. Conclusion: Regarding prognosis prediction and treatment, identifying the molecular changes in genes playing roles in prostate cancer with next-generation sequencing is very important.